Lesbian, Gay, Bisexual, and Transgender Older Adults' Experiences With Elder Abuse and Neglect. Issue 11 (21st August 2019) - Bloemen, Elizabeth M.; Rosen, Tony; LoFaso, Veronica M.; Lasky, Allison; Church, Skotti; Hall, Porsha; Weber, Tom; Clark, Sunday
Abstract : BACKGROUND/OBJECTIVES: Little is known about elder abuse and neglect in the lesbian, gay, bisexual, and transgender (LGBT) community; however, this population faces a greater risk of abuse and likely experiences abuse differently and needs different resources. We conducted focus groups to investigate LGBT older adults' perspectives on and experience with elder mistreatment. METHODS: We conducted three focus groups with 26 participants recruited from senior centers dedicated to LGBT older adults. A semistructured questionnaire was developed, and focus groups were audio recorded, professionally transcribed, and analyzed using grounded theory. RESULTS: Key themes that emerged included: definitions and etiologies of abuse, intersectionality of discrimination from multiple minority identities, reluctance to report, and suggestions for improving outreach. Participants defined elder abuse in multiple ways, including abuse from systems and by law enforcement and medical providers. Commonly reported etiologies included: social isolation due to discrimination, internalization of stigma, intersection of discrimination from multiple minority identities, and an abuser's desire for power and control. Participants were somewhat hesitant to report to police; however, most felt strongly that they would not report abuse to their medical provider. Most reported that they would feel compelled to report if they knew someone was being abused; however, they did not know who to report to. Strategies participants suggested to improve outreach included: increasing awareness about available resources and researchers engaging with the LGBT community directly. CONCLUSION: LGBT older adults conceptualize elder abuse differently and have different experiences with police and medical providers. Improved outreach to this potentially vulnerable population is critical to ensuring their safety. J Am Geriatr Soc 67:2338–2345, 2019